O papel da argumentação na zona de colaboração e criticidade - Rodrigues, Valquiria dos Santos (2010)
This study aims to understand and critically analyze not only the dialogues carried out between teachers and their pedagogical coordinator in pedagogical meetings at an accredited nursery school of the Municipality of São Paulo, but also the dialogues between the researcher-educator and the pedagogical coordinator in talks and reflective sessions, which had the discussion of the role of argumentation in critical teacher education as their main objective. For that purpose, it identifies the arguments that provide the production of a zone of collaboration and criticism as an attempt to help education professionals who are engaged in critical teacher education. The theoretical support for this research has two cores: argumentation (ARISTOTLE, 350 a.C./2005, PERELMAN and OLBRECHTSTYTECA, 1970/2005; BRETON, 2003; MOSCA, 1997/2004, 2005, 2007; OSAKABE, 1999) and critical teacher education (MAGALHÃES, 2009; LIBERALI, 1994, 2008; SCHÖN, 1992; FREIRE, 1970), both supported by the Social-Historical-Cultural Activity Theory, as discussed by Vygotsky (1924/2004, 1930/2007, 1934/2001), Leontiev (1958/1998, 1977, 1978a, 1978b), Engeström (1987, 1999) and Engeström et. al. (1999). This research is inserted in the paradigm of critical collaboration (PCcol), which makes use of action-driven investigation methods in the search for alternatives to the pattern of traditional research, as a way to offer to all participants researcher and groups connected to the research the means to efficiently answer problems of specific contexts, as well as the guidelines for a transforming action (MAGALHÃES, 2003/2007). The discussion of the results was based on selected extracts of interactions between the pedagogical coordinator and the teachers, and the pedagogical coordinator and the researcher, adding up to four activities. This discussion was grounded on the developed categories of analysis, based on Perelman and Olbrechts- Tyteca (1970/2005), Mosca (1997/2004, 2005, 2007) and Liberali (2007, 2008), and on the categories of interpretation, based on Vygotsky (1924/2004, 1930/2007, 1934/2001), Bakhtin (1934-5/1975/2002) and Magalhães (2009). The results show that the connections developed between the subjects of the research made their learning and development possible. Besides, the use of argumentation in educational moments, such as pedagogical meetings, talks and reflective sessions, enabled the production of the zone of collaboration and criticism, leading the participants to question, discuss and transform their actions